The Role of Parents and Educators in Early Childhood's Digital Literacy - Windasari, Indriana Warih; Dheasari, Agustiarini Eka (SAINTIS Publishing, 2024)
The purpose of this study is to explain how the role of parents and educators in addressing the advancement of technology is increasingly advanced. The research method used is study literature from various journals and references related to digital literacy. The results showed that the role of educators and parents in children's digital literacy are: 1) The role of educators in digital literacy is to teach basic technology skills, encourage critical thinking skills, be a role model in the use of technology, integrate technology in learning, increase understanding of cybersecurity, and collab¬orate with parents. 2) The role of parents in digital literacy is Basic Technology Assistance, En¬couraging Critical Thinking, Modeling the Use of Technology, Monitoring Regulating the Use of Gadgets, Teaching Cybersecurity Skills, and Creating a Supportive Environment. 3) The role of educators in children's digital literacy is more in terms of cognitive, affective, and social skills while parents have a role in affective and social-emotional skills in children's digital literacy.